Suboptimal Use of Effective Contraceptive Methods in Young Mexican Women With Breast Cancer - Castro-Sanchez, Andrea (J Glob Oncol, 2018)
PURPOSE: Contraceptive counseling and adherence in young women with breast cancer (BC) is a relevant issue because chemotherapy and hormonal treatment resulting in amenorrhea do not preclude unintended pregnancies. Currently, there is limited evidence from high-income countries; however, there are no studies regarding use of contraceptives in patients with BC in Mexico. This study aimed to determine the rate of contraceptive use in young Mexican women with BC during cancer treatment, characterize their contraceptive preferences, and assess contraceptive counseling by Mexican physicians. PATIENTS AND METHODS: A cross-sectional survey was conducted regarding contraceptive use and counseling among women age 40 years or younger at BC diagnosis who had completed chemotherapy in the previous 5 years or who were currently receiving long-term treatment with hormonal therapy and/or trastuzumab at a large tertiary health care facility in Mexico. RESULTS: Of a total of 104 eligible women with median age at diagnosis of 34 years, 51.1% reported using a contraceptive during chemotherapy and 45.7% reported using a contraceptive during other types of cancer treatment (hormonal therapy and trastuzumab). Of the 51 patients (49%) who were sexually active during chemotherapy, 76.5% used contraception, but only 29.4% used an effective contraceptive method. When asked about contraceptive counseling, only 16.7% recalled being advised by their health care provider. Sexually active women who received contraceptive counseling used contraceptives more often than women who were not counseled (83.3% v 22.2%). CONCLUSION: A minority of young women with BC in Mexico use effective contraception methods during cancer treatment and receive contraceptive counseling. Informing all premenopausal patients with BC about effective use of contraception methods during treatment should be an essential aspect of the supportive care of young women.